Efficient detection algorithm for 2Nx2N MIMO systems using alamouti code and QR decomposition - Arar, M.; Yongacoglu, A. (IEEE communications letters, 2006)
We propose an efficient 2Ntimes2N MIMO detection algorithm where the transmit signals are grouped in pairs and separately coded using the standard Alamouti space-time code. At the receiver, one or more QR decompositions are performed and the upper triangular property of the R matrices so obtained is exploited in order to successively decode the transmitted symbols starting with those interference-free symbols corresponding to the last two rows and columns of R. Bit-error-rate simulation results, for a 4times4 MIMO system and a bandwidth efficiency of 8 bits/s/Hz, show that the proposed technique, while less complex than ordered MMSE V-BLAST, outperforms the latter by 2-6 dB at a BER of 10 -4